Liraglutide Enhances the Activity of the ACE-2/Ang(1–7)/Mas Receptor Pathway in Lungs of Male Pups from Food-Restricted Mothers and Prevents the Reduction of SP-A - J. Fandiño; A. A. Vaz; L. Toba; M. Romaní-Pérez; L. González-Matías; F. Mallo; Y. Diz-Chaves (International Journal of Endocrinology)
In utero growth restriction and being born small for gestational age are risk factors for respiratory morbidity. IUGR (in utero growth retardation) is associated to overall reduction in lung weight, surfactant content and activity, impaired maturation of the alveolar type II cells, and decreased alveolar formation. The renin-angiotensin system (RAS) may be a key target underlying pathophysiological lung alterations. GLP-1 and agonists of its receptor modulate the expression levels of different components of RAS and also are very important for lung maturation and the production of surfactant proteins. The aim of this study was to elucidate the effects of IUGR induced by perinatal food restriction of the mother in the lung function of pups at early stages of life (PD21) and to determine if liraglutide had any effect during gestational period. Sprague-Dawley pregnant rats were randomly assigned to 50% food restriction (MPFR) or ad libitum control (CT) groups at day of pregnancy 12 (GD12). From GD14 to parturition, pregnant MPFR and CT rats were treated with liraglutide or vehicle. At postnatal day 21 and before weaning, 20 CT and 20 FR male pups were sacrificed and lungs were analyzed by RT-PCR. Liraglutide restored surfactant protein A (SP-A) mRNA expression in pup lungs from food-restricted mothers. Surfactant protein B (SP-B) mRNA expression is not affected by neither IUGR nor liraglutide treatment. Moreover, liraglutide modulated different elements of RAS, increasing angiotensin-converting enzyme 2 (ACE2) and MasR mRNA expression only in pups from food-restricted mothers (MPFR), despite food restriction had not any direct effect at this early stage. Liraglutide also increased endothelial nitric oxide synthase (eNOS) expression in MPFR lungs, reflecting the activation of MasR by angiotensin 1–7. In conclusion, liraglutide prevented the alteration in lung function induced by IUGR and promoted the positive effects of ACE2-Ang(1–7)-MasR in restoring lung function.